The complete chloroplast genome of Cyrtosia nana (Rolfe ex Downie) Garay and its phylogenetic analysis - Ding-Xiang Yu; Hai He (Mitochondrial DNA. Part B. Resources)
Cyrtosia nana is a mycotrophic orchid distributed in southwestern China and Thailand. Here, we sequenced and assembled its complete chloroplast (cp) genome using next-generation sequencing (NGS) and established a robust phylogenetic framework, providing a foundation for further studies on evolution of related taxa. The complete chloroplast genome was 85,766 bp, including a pair of inverted repeat regions (12,999 bp), a small single-copy region (14,744 bp), and a large single-copy region (45,024 bp). It encodes 47 unique genes, including 28 protein-coding genes, 16 tRNA genes, and 3 rRNA genes. Phylogenetic analysis revealed that C. nana was closely related to C. lindleyana and C. septentrionalis.